Está en la página 1de 13
f ( c) f G L c
f ( c)
f
G
L
c

.

 

 

 

ariesjuan84@ gmail.com

 

Cap´ıtulo 1

Cap´ıtulo 1 f : I → R I ⊂ R f c ∈ I f (
Cap´ıtulo 1 f : I → R I ⊂ R f c ∈ I f (

f : I R I R f

c I f ( x ) f ( c) x

c

f c Dom( f )

f ( c) c Dom( f )

l´ım

xc f ( x )

l´ım

xc f ( x ) = f ( c)

f c ∈ Dom( f ) f c Dom( f )

f ( c)

l´ım x → c f ( x ) l´ım x → c f ( x )

f ( c)

.

f f ( x ) l´ım − f ( x ) c l´ım x→c x→c
f
f ( x )
l´ım
− f ( x ) c
l´ım
x→c
x→c
f ( x )
+

f : I R I R f

c Dom( f )

f ( c) c Dom( f )

l´ım

xc

+ f ( x )

l´ım + f ( x ) = f ( c)

xc

f : I R I R f

c Dom( f )

f ( c) c Dom( f )

l´ım

xc

f ( x )

l´ım f ( x ) = f ( c)

xc

f c f

c

f c

f ( c ) l´ım

xc f ( x ) = f ( c)

l´ım

xc

f ( x ) = f ( c ) l´ım + f ( x ) = f ( c)

xc

f ( c ) l´ım

xc

f ( x ) = f ( c)

ariesjuan84@ gmail.com

.

l´ım

xc

+ f ( x ) = f ( c) f

f c

f ( c ) l´ım

xc

f ( x ) = f ( c ) l´ım + f ( x ) = f ( c)

xc

f c

f, g : R R

c Dom( f ) Dom( g )

λf c

f

± g

c

f

× g

c

f

g ( c)

= 0 c

g

f g

c

f ( c) g ( c)

[ f ± g ]( c) [ f × g ]( c)

λf ( c)

f g ( c) g ( c) = 0

l´ım

xc f ( x ) = f ( c ) l´ım

xc g ( x ) = g ( c)

xc [ f ± g ]( x ) = [ f ± g ]( c ) l´ım

l´ım

xc [ f × g ]( x ) = [ f × g ]( c)

l´ım

xc

f

g

( x ) = f ( c ) l´ım

g

xc λf ( x ) = λf ( c)

a b f

f ( x ) =

sen |x |

x

x π, 0

ax + b

x [0 , π

cos x

x [ π, 2 π

a b f

x = 0 x = π

x = 0

ariesjuan84@ gmail.com

.

f (0) = a(0) + b = b

l´ım − f ( x ) = l´ım f ( x ) = l´ım

x0

x0

sen |x |

x

= l´ım

x0

l´ım + f ( x ) = l´ım + ( ax + b ) = b + f ( x ) = l´ım + ( ax + b ) = b

x0

x0

sen( x )

x

= 1

b = 1

x = π

f ( π ) = cos π = 1

l´ım − f ( x ) = l´ım − cos π = − 1 f ( x ) = l´ım cos π = 1

xπ

xπ

l´ım − f ( x ) = l´ım − ( ax + b ) = aπ f ( x ) = l´ım ( ax + b ) = + b = 1

xπ

xπ

a = 0

a = 0 b = 1

f ( x ) = 2 + 32

x

a = 0 b = − 1 f ( x ) = 2 + 3 2

5

x 2

f R

x

= 32 f (32)

f x = 32

f (32)

l´ım

x32 f ( x )

l´ım

x32 f ( x ) = f (32)

x 5 b 5 = ( a b )( a 4 + a 3 b + a 2 b 2 + ab 3 + b 4 )

ariesjuan84@ gmail.com

.

x32 f ( x ) = l´ım

l´ım

x32

= l´ım

x32

= l´ım

x32

1

l´ım l´ım x → 32 = l´ım x → 32 = l´ım x → 32 1

2 + x 2

5

x 32 x 2

5

32 1 2 + √ x − 2 5 x − 32 √ x − 2

( x 32)( 2 + x + 2) x 32

5

4 3 2 1 5
4
3
2
1
5

( x 32)( 2

+

x + 2)( x 5 + 2 x 5 + 4 x 5 + 8 x 5 + 16)

=

5 × 2 6

f ( x ) =

 √   2 + 5  x − 2  x − 32
2 +
5
x − 2
x −
32
1
5 × 2 6

x = 32

x = 32

f ( x ) = 7 x 2 7

f

f x = 0

f (0)

x0 f ( x )

l´ım

l´ım

x0 f ( x ) = f (0)

f (0) = 7(0) 2 7 = 7

x0

l´ım f ( x )

7(0) 2 − 7 = − 7 x → 0 l´ım f ( x ) l´ım

l´ım

x0

f ( x ) 7

1

< x

< 0

7 < 7 x 2 7 < 6 7 x 2 7 =

7

l´ım

x0

7 x 2 7 = 7

l´ım + f ( x ) 0 < x < + f ( x ) 0 < x <

x0

1

7

7 < 7 x 2 7 < 6 7 x 2 7 = 7

l´ım

x0

+ 7 x 2 7 = 7

ariesjuan84@ gmail.com

.

x0

l´ım f ( x )

l´ım

x0 f ( x ) = f (0)

f

f 2

f ( 2) = 7( 2) 2 7 = 7

l´ım

x0

f ( x )

7( √ 2) 2 − 7 = 7 l´ım x → 0 f ( x )

l´ım

2 f ( x )

x

13

7

< x < 2

6

6 < 7 x 2 7 < 7 7 x 2 7 =

l´ım

x

2 7 x 2 7 = 6

l´ım 2 + f ( x ) √ 2 < x < 1 5 + f ( x ) 2 < x < 15

x

7

7

7 < 7 x 2 7 < 8 7 x 2 7 =

l´ım

x

2 + 7 x 2 7 = 7

l´ım f ( x ) x 2

f 2

a b f

f ( x ) =

 

|2 x 2 3 x 9 |

2 x 2 3 x 9

x < 3

2

x

> 3

a

b

x = 3

x = 3

2

f

x = 3 x = 3

2

x = 3

2

ariesjuan84@ gmail.com

.

f

3 = b

2

l´ım

x→− 3

2

f ( x )

2 x 2 3 x 9 = 3( x 4 ) 2 81

3

8

x

< 3

2

3( x

l´ım

x→− 3

2

|2 x 2 3 x 9 |

2 x 2 3 x 9

= 1

3

4 ) 2 81

8 >

0

b = 1

x = 3

a = 1

f

:

I

R R f

c

I

f

c

f

l´ım

xc f ( x ) = L

f ( c) = L

f ( c) f L G c
f ( c)
f
L G
c

f

ariesjuan84@ gmail.com

.

f

l´ım + f ( x )

xc

l´ım

xc

f ( x )

f

l´ım

xc

+ f ( x ) = ∓∞

l´ım f ( x ) = ±∞

xc

f f ( c) c
f
f ( c)
c
f c
f
c

f

f ( x ) = x 3 2 x 2 11 x + 12 x 2 5 x + 4

f ( x ) = ( x 4)( x 1)( x + 3) ( x 4)( x 1)

x = 4 x = 1

f ( x ) = x + 3

x 1 4

f ( x ) =

1

2 cos x x 2

1

x ) =      1 2 − √ cos x x 2

8

x

x = 0

= 0

x = 0

f (0) = 1

8

ariesjuan84@ gmail.com

.

1

x0 2 cos x

x 2

l´ım

1

x0 2 cos x x 2

l´ım

l´ım 1 x → 0 2 − √ cos x x 2 l´ım 1 = l´ım

1

= l´ım

x0 (1 + 1 cos x)

2x 2

1 cos x

2

x 2

l´ım

x0

l´ım

= e

1

8

sen x

= 2 x 2 (1 + cos x)(1 + cos x )

e

= e

x0

f ( x ) = 1 + 2

1

x

x = 0

l´ım + (1 + + (1 +

x0

l´ım − (1 + (1 +

x0

2

2

1

x ) =

+

1

x ) = 1

x = 2 x = 2

f

f ( x ) =

x 2 5 x

2

1 x 3

x + 1

2 x 2

x < 2

x > 2

x = 2 x = 2

x = 2

f ( 2)

f ( 2) = ( 2) 2 5 2

2

= 3

l´ım

x→−2 f ( x )

ariesjuan84@ gmail.com

.

x→−2 + x 2 5 x

2 = 3

x → − 2 + f ( x ) = l´ım x2 + f ( x ) = l´ım

l´ım

2 x ≤ − 1 1 x

2

1

2

x

2

= 1

x → − 2 − f ( x ) = l´ım x2 f ( x ) = l´ım

l´ım

x2 1 x 3 = 9

f x = 2

x = 2

ariesjuan84@ gmail.com